Potentials and possibilities of branding intangible cultural heritage using the example of Šibenski botun - Schildenfeld, Ivana (Array, 2020)
The tourist market is expanding quickly and tourists are becoming more demanding and selective. Therefore, tourism requires creating an image and a brand based on an authentic identity by using innovative and enticing ideas that will result in attracting the attention of target audiences. “Šibenski botun” with its historical, social and cultural potential, as cultural heritage represents an ideal platform for the branding process and the development of cultural tourism. To begin with the branding process, it was necessary to explore the perception of the local community as one of the primary audiences. To this end, a questionnaire was used as a measuring instrument in the data collection method on a previously selected sample. The study confirmed a hypothesis that Šibenik residents were not perceiving “Šibenski botun” as the city’s brand, but as an extremely important souvenir. Using three structured interviews possibilities and potentials of “Šibenski botun” have been studied for the purpose of the branding process.